Memperkuat Fungsi dan Peran Pengawasan Badan Permusyawaratan Desa (BPD) Melalui Advokasi Hak Warga atas Informasi Publik Untuk Membangun Tata Kelola Pemerintahan Desa - Rochmad Effendy (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
Unlike during the New Order era which saw village as an extension of the central government without adequate authority to run the village government, village now has recently become self -governing community equipped with broad authority to manage their own affairs for the sake of realizing people’s welfare. It is an entity of community combined with government. It is community who possesses special governmental organizational structure with unique and vast authority to carry out development programs. In doing so, they handle themselves autonomously based on their own cultural values, their initiatives. As such, the central government has nothing but to respect and concede the uniqueness of its each respective village across the nation. In addition, central government has to allocate state budget to realize social and economic justice for more than 17,000 villages. This is the way the Village Law No 6 2014 has designed which differs dramatically from the previous village law. It has adopted recognition and subsidiarity principle in managing village development. In order this to materialize, Village Council whose membership consists elected representatives from among the villagers prominent figures has been empowered its political roles by means of annulling its inherent legislative authorities. To pave the way, it is positioned outside the formal village government organizational structure which makes it fit to function as representative of villagers civil organization. Given this setting, the Council’s main duty is to fight to people’s interest by preventing themselves from village government vested political interest. To make things better, the law has authorized it to organize a strategic villagers gathering held annually namely Village Meeting. As the key actor of the meeting, the council members has to show off their capacities in political communication as well as public communication to run village democratic governance whose operating values are transparency and accountability. For this to occur, advocating people’s information rights is necessary requirement. By so doing, those values will institutionalize within village government daily operations by establishing Public Information and Archives Operator as required by Public Information Transparency Law No 11 2008 which will bring about good village governance.DOI: https://doi.org/10.26905/pjiap.v2i1.1447